Convenient Titanium(III)‐Catalyzed Synthesis of Cyclic Aminoketones and Pyrrolidinones—Development of a Formal [4+1] Cycloaddition1. Issue 28 (5th June 2013) - Frey, Georg; Luu, Hieu‐Trinh; Bichovski, Plamen; Feurer, Markus; Streuff, Jan
<x xml:space="preserve">Abstract</x> Have it both ways: α‐Aminated ketones can be prepared by the titanium(III)‐catalyzed reductive radical cyclization of iminonitriles. Depending on the position of the nitrile at the imine carbon or nitrogen, cyclic aminoketones or pyrrolidin‐3‐ones with a tetrasubstituted α‐carbon can be formed in up to quantitative yield. In the latter case, the imine condensation and TiIII catalysis correspond to a formal [4+1] cycloaddition.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>